Property rights according to the civil code in Indonesia - Pratiwi, Desi; Luthviah, Shiva Durrotu; Muid, Abdul; Marina, Siti; Maulana, Ayang Fristia (Institute Of computer Science (IOCS), 2025)
This study discusses the basic concept of property rights in the legal system civil law in Indonesia which refers to the Indonesian Civil Code Civil Code (Civil Code). This study examines the fundamental concept of property rights in Indonesia's civil law system, referencing the Indonesian Civil Code (KUHPerdata). Property rights constitute a legal relationship between legal subjects and objects, granting owners direct authority to control, utilize and benefit from the property